Numerical and experimental study of pulsatile flow in bi-leaflet mechanical heart valves - Shi , Yubing. (2008)
This research project is aimed towards a better understanding of the flow field structure of a bi-leaflet mechanical heart valve (MHV) operating under simulated physiological condition. In the past, much research has been carried out to study the flow in heart valves with computational fluid dynamics (CFD) and particle image velocimetry (PIV) experimental methods.